Longitudinal patient-oriented outcomes in neuropathy: Importance of early detection and falls. (7th July 2015) - Callaghan, Brian; Kerber, Kevin; Langa, Kenneth M.; Banerjee, Mousumi; Rodgers, Ann; McCammon, Ryan; Burke, James; Feldman, Eva
Abstract : Objective: To evaluate longitudinal patient-oriented outcomes in peripheral neuropathy over a 14-year time period including time before and after diagnosis. Methods: The 1996–2007 Health and Retirement Study (HRS)–Medicare Claims linked database identified incident peripheral neuropathy cases ( ICD -9 codes) in patients ≥65 years. Using detailed demographic information from the HRS and Medicare claims, a propensity score method identified a matched control group without neuropathy. Patient-oriented outcomes, with an emphasis on self-reported falls, pain, and self-rated health (HRS interview), were determined before and after neuropathy diagnosis. Generalized estimating equations were used to assess differences in longitudinal outcomes between cases and controls. Results: We identified 953 peripheral neuropathy cases and 953 propensity-matched controls. The mean (SD) age was 77.4 (6.7) years for cases, 76.9 (6.6) years for controls, and 42.1% had diabetes. Differences were detected in falls 3.0 years before neuropathy diagnosis (case vs control; 32% vs 25%, p = 0.008), 5.0 years for pain (36% vs 27%, p = 0.002), and 5.0 years for good to excellent self-rated health (61% vs 74%, p < 0.0001). Over time, the proportion of fallers increased more rapidly in neuropathy cases compared to controls ( p = 0.002), but no differences in pain ( p = 0.08) or self-rated health ( p = 0.9) were observed. Conclusions: In older persons, differences in falls, pain, and self-rated health can be detected 3–5 years prior to peripheral neuropathy diagnosis, but only falls deteriorates more rapidly over time in neuropathy cases compared to controls. Interventions to improve early peripheral neuropathy detection are needed, and future clinical trials should incorporate falls as a key patient-oriented outcome.